Glaciozyma antarctica M. Groenew. & Q. M. Wang 2020, comb. nov. - Li, A. - H.; Yuan, F. - X.; Groenewald, M.; Bensch, K.; Yurkov, A. M.; Li, K.; Han, P. - J.; Guo, L. - D.; Aime, M. C.; Sampaio, J. P.; Jindamorakot, S.; Turchetti, B.; et al. (Zenodo, 2020)
Glaciozyma antarctica (Fell, Statzell, I.L. Hunter & Phaff) M. Groenew. & Q.M. Wang, comb. nov. MycoBank MB831870. Basionym : Leucosporidium antarcticum Fell, Statzell, I.L. Hunter & Phaff, Antonie van Leeuwenhoek 35 (4): 447 (1970). Synonym : Glaciozyma antarctica (Fell, Statzell, I.L. Hunter & Phaff) Turchetti, Connell, Thomas-Hall & Boekhout, Extremophiles 15 (5): 579 (2011), nom. inval. , Art. 41.5, see Note 1 (Shenzhen). Published as part of Li, A. - H., Yuan, F. - X., Groenewald, M., Bensch, K., Yurkov, A. M., Li, K., Han, P. - J., Guo, L. - D., Aime, M. C., Sampaio, J. P., Jindamorakot, S., Turchetti, B., Inacio, J., Fungsin, B., Wang, Q. - M. & Bai, F. - Y., 2020, Diversity and phylogeny of basidiomycetous yeasts from plant leaves and soil: Proposal of two new orders, three new families, eight new genera and one hundred and seven new species, pp. 17-140 in Studies In Mycology 96 on page 134, DOI:10.1016/j.simyco.2020.01.002, http://zenodo.org/record/10497182